Ethical considerations related to the management of cancer research samples - Castañeda, Carlos A. (2019)
Molecular analysis of human biological material allows the identification of future biomarkers to improve the management of patients with cancer. However, the handling of these samples requires particular ethical considerations. Different organizations such as the European Council and government agencies of the United States have generated different documents with definitions, mechanisms, and regulations to avoid putting at risk of harm or violating the rights of donors of biological samples. Finally, all these documents have evolved over time and have allowed research institutions to have standard committees and regulations in ethics. Thus, legal institutions can create precedents and generate coherent sentences.